2018
DOI: 10.1002/2211-5463.12537
|View full text |Cite
|
Sign up to set email alerts
|

Utility of GDF‐15 as a diagnostic biomarker in gastric cancer: an investigation combining GEO, TCGA and meta‐analysis

Abstract: It was recently suggested that growth differentiation factor‐15 ( GDF ‐15) is associated with gastric cancer ( GC ) carcinogenesis. However, the diagnostic potential of GDF ‐15 for GC remains unclear. To address this issue, we obtained RNA sequencing and microarray data from the Gene Expression Omnibus ( GEO ) and The Cancer Genome Atlas ( TCGA ) datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…By benefiting from a substantial number of expressed genes and clinical data regarding cancer patients in a public online database, many novel genes have been identified that are aberrantly expressed and have good clinical benefits in human cancers. For instance, a meta-analysis of data accessed from the GEO database showed that low TUBA4B levels were closely associated with short OS in various human cancers, which indicated that TUBA4B could be a novel prognostic biomarker for cancer patients.19 Also, using SROC curve analyses based on information downloaded from TCGA and GEO databases, CTD-2547G23.4 was found to have good diagnostic value for HCC patients,20 and GDF-15 was shown to have good diagnostic value for gastric cancer patients.21…”
Section: Discussionmentioning
confidence: 99%
“…By benefiting from a substantial number of expressed genes and clinical data regarding cancer patients in a public online database, many novel genes have been identified that are aberrantly expressed and have good clinical benefits in human cancers. For instance, a meta-analysis of data accessed from the GEO database showed that low TUBA4B levels were closely associated with short OS in various human cancers, which indicated that TUBA4B could be a novel prognostic biomarker for cancer patients.19 Also, using SROC curve analyses based on information downloaded from TCGA and GEO databases, CTD-2547G23.4 was found to have good diagnostic value for HCC patients,20 and GDF-15 was shown to have good diagnostic value for gastric cancer patients.21…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated production of MIC-1 is triggered in response to inflammation such as tissue injury, biomechanical stress, and anoxia [8, 9]. MIC-1 has been considered to play a pivotal role in the development and progression of many diseases such as cardiovascular diseases and malignant cancer [1012]. Recently, MIC-1 is considered as a long-term metabolism regulator with a function of increasing lipolysis as an adipokine in a paracrine fashion [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Adopting a similar method, reports on microarray datasets have led the discovery of novel biomarkers in thyroid cancer, gastric cancer and head and neck cancer (Liu et al, 2018;Reddy et al, 2016;Zhao and Li, 2018). This is also translated in clinics to predict recurrence and treatment outcome in breast cancer (Ademuyiwa et al, 2011;Madden et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…*For Correspondence: prabhudas.patel@gcriindia.org Kinjal D Patel, Hemangini H Vora, Prabhudas S Patel* expression omnibus (GEO) and array express along with advanced computational data analysis tools such as GeneSpring GX, INMEX and R/Bioconductor allow us to congregate and re-examine gene expression data in a single experiment. Ergo, various groups have effectively extracted significant insights using meticulous analytical strategies (Liu et al, 2018;Reddy et al, 2016;Zhao and Li, 2018). Here, to overcome the aforementioned limitations, we integrated single chip microarray data (HG-U133_Plus_2) and stratified normal samples into two classes: healthy normal tissues and adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%